KEMAMPUAN DAYA TETAS TELUR (Hatching Rate) IKAN PATIN (Pangasius Hypophthalmus) DALAM AQUARIUM DENGAN PERLAKUAN TEMPERATUR YANG BERBEDA - Mukhlisah (Fakultas Pertanian UVAYA Banjarmasin, 2022)
Catfish (Pangasius hypopthalmus) culture is very potencial to be develop. One of the critical success factors is the success of cultivition is the availability of good a seeds in sufficient quantities and sustainable. Temprature is one of the factors that influence the hatch ability of eggs. The experiment used a completly randomized design (CRD) method, consisting of three treatments and three replications. The order of treatment was A 27˚C, B 29˚C dan C31˚C. The result of research for each treatment A, B, and C indicate that avarage of hatching rate ware 67%, 68% and 71%. Data analysis uses variance test (ANOVA). The result showed the temperature did not significantly